Legal aspects of the association of overseas countries and territories with the European Union - Ivan Hruškovič (DANUBE: Law, Economics and Social Issues Review, 2014)
This article is concerned with an issue in European law that is historically derived from the Treaty establishing the European Economic Community. The aim is to illuminate the functions and objectives of the European Union that correspond to the provisions of Part Four of the Treaty on the Functioning of the European Union - Association of the Overseas Countries and Territories. The basic provisions are laid down in the primary law of the European Union but there are also other documents and legislative acts that lay down more detailed provisions on the given issue and reveal a more complex perspective. The article focuses on the existing legislation regulating the association of overseas countries and territories with the Union. The author first draws attention to the key provisions of the Treaty establishing the EEC that define the purpose, objectives and fundamental principles applied between the Union and the overseas countries and territories. The main purpose of the article, however, is to analyse the current legal basis of association and to highlight the need for a new legislative framework of cooperation. New legislation should take into account not only the interests of the Union, but also the desire of the overseas countries and territories for a new quality of mutual cooperation. The author argues that the best way to improve the association mechanism based on the Lisbon Treaty is to modernise the Union's existing secondary legislation in this area. In this regard the author analyses issues related to Council decision 2001/822/EC on the association of the overseas countries and territories with the European Community and the proposal for a Council decision (COM/2012/362) of 16 July, 2012.
Keywords: 330; European Union; European Law; Primary Law; Council Decisions; Association of Overseas Countries and Territories